2001
DOI: 10.1074/jbc.m106017200
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Prolyl Oligopeptidase Tc80 Is Involved in Nonphagocytic Mammalian Cell Invasion by Trypomastigotes

Abstract: Trypanosoma cruzi is an intracellular protozoan parasite able to invade a wide variety of mammalian cells. To have access to the target organs/cells, the parasite must cross the basal laminae and the extracellular matrix (ECM). We previously characterized an 80-kDa proteinase (Tc80) secreted by the infective trypomastigotes that hydrolyzes native collagens and might be involved in infection by degrading ECM components. Here, we present evidence indicating a role for Tc80 in the invasion of nonphagocytic cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 51 publications
1
108
0
7
Order By: Relevance
“…Recent studies have shown that an 80-kDa serine protease located inside a vesicular compartment close to the flagellar pocket was found to hydrolyze FN and, more importantly, to be a potential target for a potent selective inhibitor that blocks T. cruzi entry into host cells (8,14). Also, a new member of the T. cruzi 80-85-kDa glycoprotein family was shown to bind to LN (15).…”
Section: Trypanosoma Cruzi-host Cell Interactionmentioning
confidence: 99%
“…Recent studies have shown that an 80-kDa serine protease located inside a vesicular compartment close to the flagellar pocket was found to hydrolyze FN and, more importantly, to be a potential target for a potent selective inhibitor that blocks T. cruzi entry into host cells (8,14). Also, a new member of the T. cruzi 80-85-kDa glycoprotein family was shown to bind to LN (15).…”
Section: Trypanosoma Cruzi-host Cell Interactionmentioning
confidence: 99%
“…Curiously, all the analyzed closely related parasitic trypanosomatids, as well, as Cryptobia salmonistica, reveal through gelatin-SDS-PAGE only metallo-and cysteine peptidases, which are prototypal peptidases and virulence factors. In trypanosomatids, for instance, serine peptidases can only be detected by in-solution assays or after enrichment processes (Grellier et al 2001). It is somewhat intriguing that cysteine and metallopeptidases are either not resistant to the denaturation/refold process and/or are not abundantly expressed by this free living bodonid, because they were not detected by zymography.…”
Section: Practical Examples Of Peptidases Screening Through Sds-page-mentioning
confidence: 99%
“…A member of the prolyl oligopeptidase (POP) family of serine proteases, with specificity for human collagen types I and IV, has been identified in cell-free extracts of trypomastigotes, amastigotes and epimastigotes (84)(85). The 80 kDa enzyme, denominated POP Tc80, also hydrolyses fibronectin and appears to be implicated in host cell invasion.…”
Section: Prolyl Oligopeptidasementioning
confidence: 99%